Advanced statistical mechanics - McCoy, Barry M. (Oxford : Oxford University Press, 2010)
McCoy presents the advances made in statistical mechanics over the last 50 years, including mathematical theorems on order and phase transitions, numerical and series computations of phase diagrams and solutions for important solvable models such as Ising and 8 vortex.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Statistical mechanics